Reform of the European Court of Human Right - Mojsilović, Marijana D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The European Court of Human Rights is the crown in the international system for protecting human rights. In recent years the Court has become a victim of its own success. In response to growing backlog of individual complaints, the Council of Europe has, over the last five years, considered numerous proposals to restructure the European human rights regime and redesign the European Convention on Human Rights. The aim of this article is just to show the most important innovations introduced primarily by Protocol no. 14, and then the Declarations adopted at the Conference in Interlaken, Izmir and at the end in Brighton, this year. Some of the solutions provided will help to reduce the work load of the Court in the future, while others are introduced for practical reasons, or a well-known political. However, adopted proposals should be given time to show some results. But in the other way, the frequent changes in the Court´s work system and in the Convention system may prove to be a new problem. An institution such as the Court, the protector of human rights at the European level should not be allowed to suffer frequent “eartquakes”. It should be let alone to work quietly and without “turbulence”.